Precise long non-coding RNA modulation in visual maintenance and impairment. Issue 7 (21st December 2016) - Wan, Peixing; Su, Wenru; Zhuo, Yehong
Abstract : Long non-coding RNAs (lncRNAs) are remarkably powerful, flexible and pervasive cellular regulators. With the help of cheaper RNA-seq, high-throughput screening of lncRNAs has become widely applied and has identified large numbers of specific lncRNAs in various physiological or pathological processes. Vision is known to be a complex and vital perception that comprises 80% of the sensory information we receive. A consensus has been reached that normal visual maintenance and impairment are primarily driven by gene regulation. Recently, it has become understood that lncRNAs are key regulators in most biological processes, including cell proliferation, apoptosis, differentiation, immune responses, oxidative stress and inflammation. Our review is intended to provide insight towards a comprehensive view of the precise modulation of lncRNAs in visual maintenance and impairment. We also highlight the challenges and future directions in conducting lncRNA studies, particularly in patients whose lncRNAs may hold expanded promise for diagnostic, prognostic and therapeutic applications.